PENGARUH MEDIA PEMBELAJARAN KARTU KATA TERHADAP MOTIVASI DAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS 1 UPTD SDN POLONGAN - Faizah, Nur; Firmansyah, Ihwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is part of the Elementary School Teacher Education Study Program supervised by Ihwan Firmansyah. This study aims to determine the effect of using word card learning media on the motivation and learning outcomes of first-grade students at the UPTD SDN Polongan. The background of this research is based on the low motivation and learning outcomes of students in the Indonesian Language subject, so that innovations in learning media are needed that are more interesting, interactive, and in accordance with the characteristics of elementary school students. The method used in this research is quantitative research with a one-group pretest-posttest design. This design is used to see changes in student conditions before and after being given treatment in the form of using word card learning media. Data collection techniques are carried out through learning outcome tests and learning motivation questionnaires. Before being used, the research instrument was first tested for validity and reliability to ensure the instrument's feasibility in collecting research data. Data analysis was carried out using a normality test and a paired sample t-test to determine the level of significance of changes that occur after being given treatment. The results of the paired sample t-test on learning outcomes showed a significance value of 0.000 (<0.05), so it can be concluded that the word card learning media has a significant effect on improving students' Indonesian language learning outcomes. In addition, the results of the paired sample t-test on learning motivation also obtained a significance value of 0.000 (<0.05), indicating that the use of word cards has a positive effect on students' learning motivation in learning Indonesian. The results of this study prove that the use of interactive learning media, such as word cards, can help improve the motivation and learning outcomes of elementary school students, especially in the Indonesian language subject in lower grades.